Qualitative research [ challenging the orthodoxies in standard academic discourse(s) - Kouritzin, Sandra G.; Norman, Renee , 1950-; Piquemal, Nathalie A. C. (Inquiry and pedagogy across diverse contexts, 2009)
Evocative and provocative, this book presents the points of view of (often junior) scholars in the social sciences whoused non-standard methods or writing practices to challenge the "research-as-usual" paradigm in the academy. The authors discuss their lived personal experiences, as well as their struggles and eventual successes.